PEMUTUSAN HUBUNGAN KERJA SEPIHAK (STUDI KASUS TERHADAP PUTUSAN HUBUNGAN INDUSTRIAL NOMOR 170/PDT.SUS-PHI/2020/PN.JKT.PST) - Dhea Dillah Probokusumo; Gunardi Lie (Fakultas Hukum Universitas Tarumanagara, 2021)
A one sided Termination of Employment Relationship is something that occurs due to something that results in the termination of the rights and obligations between the worker/labourer and the entrepreneur. In termination of employment sometimes disputes arise because there is no common understanding between workers/laborers and employers.. The settlement of dismissal disputes can be carried out by Bipartite, Mediation, Conciliation, Arbitration, and the Industrial Relations Court. Cases of unilateral termination of employment often increase from year to year. However, not a few cases were enforced unfairly, and harmed the workers and workers. The research method used is to regulate justice through the use of legal methods and conceptual methods. From the results of this study, the authors raised the formulation of problems related to the role of the Panel of Judges in upholding the truth, and related to unilateral termination of employment related to the rejection of mutations, especially to parties affected by a breach of contract against the work contract that binds the party This study aims to find out how the implementation of unilateral termination of employment disputes at the Industrial Relations Court and to find out what obstacles occur and provide solutions to these obstacles.